The fruits of madness : perspectives on the prophetic movements in three traditions : essays from the seminar in Biblical characters in Judaism, Christianity, Islam and in literature /: perspectives on the prophetic movements in three traditions : essays from the seminar in Biblical characters in Judaism, Christianity, Islam and in literature. (2016) - Unknown
No abstract available